THEORETICAL FOUNDATIONS OF PSYCHOLOGICAL SERVICE - Ungboyeva Umida Sayfullayevna (American Journals Publishing, 2023)
The article analyzes the theoretical foundations of psychological services, scientific research conducted by our and foreign scientists, ideas about individual psychological differentiation and theories aimed at understanding and understanding the inner world of a person.
Keywords: Psychological service, need, stages of need, information, humanistic theory, psychoanalysis, cognitive dissonance, defense mechanism, motivation, congruence, deficit.